Motorcycle Financing Transactions at PT Bank Sumut Syariah Panyabungan Sub-Branch: Islamic Law Perspective - Siti Kholijah (Budapest International Research and Critics University, 2022)
The main principle of islamic life is monotheism of Allah, namely an awareness that human life is a mandate from Allah. The word muamalat is the only word that literally means